Development of A Program Theory on The Success in Research of Faculties: A Multiple Case Study of TRF-CHE Outstanding New Researchers in Social Science and Humanities - Lamaisie, Warayost; Srisukvatananan, Pawinee; Tobua, Suntara (Scholar: Human Sciences, 2016)
The objective of this research is to develop the program theory of successful researchers based on Chen’s change model, which includes 3 components to the success: interventions, determinants and outcomes. The research is done by studying 3 selected cases who received awards for The Thailand Research Fund and Office of the Higher Education Commission. The research process includes the following steps: 1) set up preliminary change model using concepts from related theory and research 2) develop interview questions and gather verifications to explain interventions and determinants in the change model and supporting success factors 3) collect data according to the nature of variables. 4) analyze data of each case individually, and 5) synthesize multiple cases to modify change model for success and find conclusion for the program theory of successful researchers. The research results indicate that the program theory of successful researchers, which is developed based on Chen’s change model, can be explained with the research outcomes of awarded researchers. The main 3 potentials of their success are self-development, language skills and research skills. The supporting factors for the success are good companions who support knowledge and inspiration, and the organization that allows flexibility and freedom of thoughts and provides full supports for research.